100 Resilient Cities program and the role of the Sendai framework and disaster risk reduction for resilient cities. (October 2021) - Hofmann, Sahar Zavareh
Abstract: The Rockefeller Foundation launched 100 Resilient Cities (100RC) in 2013 to build worldwide urban resilience. The 100RC program aims to implement urban resilience under the Sustainable Development Goals of the UN 2030 Agenda for Sustainable Development and the Sendai Framework for Disaster Risk Reduction 2015–2030. These frameworks link disaster resilience and disaster risk reduction to issues of vulnerability, climate change, livelihoods, rebuilding, and equity. Achieving disaster resilience and risk reduction requires more than building back better, or bouncing back from disaster: social equity, participation and livelihoods must also be advanced. Using a pathways approach related to narratives of disaster vulnerability and risk, this paper analyzes the resilience policies developed to support disaster risk reduction under the program. Evaluating member city Resilient Strategies plans using directed and summative content analysis, this research assesses whether the 100RC program emphasized vulnerability and risk narratives in its disaster risk reduction approaches. These results reveal the differences produced among member cities – and from expectations of advancing social equity, livelihoods and participation – due to the role of actors and power expressed in the policy design and implementation. The paper concludes with recommendations to support urban disaster resilience using the Sendai Framework. Highlights: 100 Resilient Cities Program evaluation prioritizing disaster risk reduction. Results find the 100RC focus is fragmented addressing city vulnerabilities and disaster risks. 100RC program highlights imbalances of power and roles of actors in the creation of urban resilient institutions, infrastructures and networks.